Ausgewählte Probleme des wissenschaftlichen Instrumentariums der wirtschaftsgeschichtlichen Forschung am Beispiel der Studien über den Wirtschaftswandel Polens in den 90er Jahren des 20. Jahrhunderts [Selected problems of the scientific instruments of economic history research using the example of studies on the economic transition of Poland in the 1990s] - Grala, Dariusz (Studia Historiae Oeconomicae, 2009)
This paper presents specific problems of research into contemporary history, with particular emphasis on the analysis of economic sources. In addition, the author proposes his own classification of economic sources and their role in communication with specific recipients. The problems mentioned relate mainly to aspects of contemporary Polish history that are in the author's area of ​​scientific interest.